Proposed Patient Information System for Dialysis Center (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
A patient information system will help Eagle Rock Dialysis Center to manage the information of patients and categorized the medicines or equipment to use. This system will help the administration to know the background of the patient in case of an emergency. The researchers created a system for the company that is user-friendly in finding the patient’s sickness. The patient information system is secure and cannot be hacked. They accept the patients they will interview and ask if they have PhilHealth membership, which is the most important requirement in the dialysis center. The goals of Eagle Rock Dialysis Center are to help patients have a long life. The process of the dialysis center starts with the acceptance of the patient get his/her medical records from the hospital who requested the dialysis and if the patient is a member of PhilHealth or a medical health cardholder. The proponents used the systems development life cycle in developing the system. As the proponent’s approach and methodology, the patient information system flowed in five processes. First, the researchers sought a client, and then they created plans and timelines for the proposed system. Second, the researchers surveyed the target client and collected all the data needed by the system project. Third, the researchers designed a system that the user will easily recognize. Fourth, the researchers implemented the proposed system and tested it to ensure that it will function properly. The fifth stage was maintaining the system to be in a good working condition. The researchers developed the following deliverables: (1) login page, which is only for the administrators of the dialysis center to secure all information about the patient; (2) table page, which contains the list of all registered patients; (3) add a page, which is where new patients are added with their corresponding history; (4) update page, which includes the addition of patient’s information; and (5) settings page, which is for the user and contains the patient’s history. The computerized patient information system will create an easier and convenient way of administration and help the client find the patient’s names and their important details easily. The system focused on the confidentiality of data collected from the time of acceptance to patient’s recovery or end of treatment to ensure the security of the confidential information of the dialysis center patients. The system will help the administration to easily find patient’s information.
Keywords: information patient dialysis center